2018
DOI: 10.1007/s40123-018-0124-z
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Conservative Management for a Roller-Coaster-Related Vitreous Haemorrhage

Abstract: The purpose of this report is to describe the case and management of an unexplained vitreous haemorrhage that occurred after repeated roller-coaster riding. The authors inadvertently demonstrate the value of observation over immediate surgery in certain situations and review the literature on vitreoretinal and other ocular complications after roller-coaster riding. A 26-year-old male presented 12 h after riding high-velocity roller-coasters with a left vitreous haemorrhage. A hazy view of the retina and B-scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…She also had a brief history of severe coughing before the onset of vision loss, and we hypothesized that her condition may have been due to the presence of a small retinal cyst prior to the severe coughing, which was stimulated by severe coughing and resulted in enlargement of the cyst and rupture of the cyst and hemorrhage. Alexander et al [11] also reported a case of retinoschisis with intraretinal cyst hemorrhage due to roller coaster riding. Keith [1] and Sen and Mishra [6] reported a similar case of retinal cleavage with a large retinal cyst.…”
Section: Discussion Andmentioning
confidence: 98%
See 1 more Smart Citation
“…She also had a brief history of severe coughing before the onset of vision loss, and we hypothesized that her condition may have been due to the presence of a small retinal cyst prior to the severe coughing, which was stimulated by severe coughing and resulted in enlargement of the cyst and rupture of the cyst and hemorrhage. Alexander et al [11] also reported a case of retinoschisis with intraretinal cyst hemorrhage due to roller coaster riding. Keith [1] and Sen and Mishra [6] reported a similar case of retinal cleavage with a large retinal cyst.…”
Section: Discussion Andmentioning
confidence: 98%
“…Currently, the treatment of retinal cysts has been reported to be inconsistent. Cai et al [10] concluded that vitrectomy combined with retinotomy is very effective in removing large cysts and providing adequate relief from retinal traction, but Brent et al [11] emphasized that there is still a place for conservative treatment. This case report describes the use of scleral buckling with external compression combined with external drainage of intracystic uid for the treatment of a large intraretinal cyst with retinal cleavage.…”
Section: Discussion Andmentioning
confidence: 99%
“…[8][9][10] Currently, the treatment of retinal cysts has been reported to be inconsistent. Cai et al [11] concluded that vitrectomy combined with retinotomy is very effective in removing large cysts and providing adequate relief from retinal traction, but Brent et al [6] emphasized that there is still a place for conservative treatment. This case report describes the use of scleral buckling with external compression combined with external drainage of intracystic fluid for the treatment of a large intraretinal cyst with retinal cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…She also had a brief history of severe coughing before the onset of vision loss, and we hypothesized that her condition may have been due to the presence of a small retinal cyst prior to the severe coughing, which was stimulated by severe coughing and resulted in enlargement of the cyst and rupture of the cyst and hemorrhage. Alexander et al [ 6 ] also reported a case of retinoschisis with intraretinal cyst hemorrhage due to roller coaster riding. Keith [ 1 ] and Sen and Mishra [ 7 ] reported a similar case of retinal cleavage with a large retinal cyst.…”
Section: Discussionmentioning
confidence: 99%